If you hopped like a frog - Schwartz, David M.; Warhola, James (New York : Scholastic Press, 1999)
Introduces the concept of ratio by comparing what humans would be able to do if they had bodies like different animals.
School Library Journal, November 1999.
Book Links (A.L.A.), November 2004.
Publisher's Weekly, August 1999.
Booklist, November 1999.
Bulletin (Center for Children's books), December 1999.
Appraisal-Science Books for Young People, June 2001.
Keywords: Ratio and proportion -- Juvenile literature; Ratio and proportion; Anatomy, Comparative; Ratio and proportion; Comparative anatomy; Ratio and proportion; Anatomy, Comparative